In a Boat on the River Nowhere Writing Home:: The Spiritual Poetic of Tim Lilburn - Maillet, Gregory (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
Tim Lilburn's ninth book, the 2003 Governor General's award-winning Kill-site, is grounded not only in the harsh, rural Saskatchewan landscape that he calls home, but also in a philosophical and theological poetics that draws on multiple ancient eastern and western sources. Lilburn's essays of the 1990s, collected in Living in the World as if it were Home in 1999, provide insight into this poetics, including his perspectives on nature, the contemplation of God, and the idea of knowledge as the darkening of the mind. An understanding of these themes is essential to a critical appreciation of his poetry. The central spiritual conflict or dialectic in Lilburn's poetry is between the presence and absence of the divine in the world. Despite this constant tension, the negative or absence takes precedence, and his poetic emerges in Kill-site as concrete and anti-transcendental.